Peptides, new tools for plant protection in eco-agriculture - Yi-Meng Zhang; De-Xing Ye; Yan Liu; Xin-Yuan Zhang; Yuan-Lin Zhou; Li Zhang; Xin-Ling Yang (Advanced Agrochem, 2023)
As important physiological regulators, peptides have been used in many fields including medicine, cosmetics, healthcare products, animal nutrition and health, and plant nutrition and protection. In recent years, peptides have become a popular research subject in plant protection as antimicrobial and immune inducers, plant growth regulators, insecticides, and herbicides for their extensive raw material sources, excellent activity, and ideal environmental compatibility. This paper briefly introduces peptide research progress, presents an overview of peptide studies in plant protection, and summarizes the application of the peptides in plant protection and prospects for peptides as green agrochemicals.